TANGGAP BIBIT KARET (Hevea brasiliensis Mull. Arg) TERHADAP PEMBERIAN MIKORIZA VESIKULAR ARBUSKULAR DAN PUPUK FOSFOR DI POLYBAG Rubber Seedling Response (Hevea Brasiliensis Mull. Arg) To The Application Of Vesicular Arbuscular Mycorrhizae and Phosphorus F - Elis Kartika; Helmi Salim; . Fahrizal (Bioplantae, 2013)
This research was conducted to determine the response of rubber seedlings to the application of vesicular arbuscular Mycorrhiza (VAM) and phosphorus (P). The design used in this study was completely randomized design (CRD) with two factors: VAM and phosphorus doses. The treatment is VAM doses consisting of 3 levels of mycorrhiza, that is, without mycorrhizae, 10 g/polybag , 20 g/polybag and the provision of phosphorus which consists of 5 levels i.e. without phosphorus, 25% of the recommended dose, 50% of the recommended dose, 75% of the recommended dose , 100% of the recommended dose. Each treatment was repeated 3 times so that there are 45 units of the experiment. Thevariables observed were seedlings height, seedling, diameter, total leaf area, leaf number, root dry weight, shoot dry weight, and percentage of mycorrhizal infection. The results showed that the mycorrhizal 10 g/polybag and 75% of phosphorus of the recommended dose is the best dosage on the growth of rubber seedlings.Key words : Rubber seedling, VAM, Phosphorus